The Triumph of the “Therapeutic” in Quebec Courts: Mental Health, Behavioural Reform and the Decline of Rights - Bernheim, Emmanuelle (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2022)
In the Canadian province of Quebec, the role of the courts is crucial in civil, criminal or administrative proceedings concerning mental health: the courts must ensure both public safety and the protection of the rights of defendants. Therapeutic-jurisprudence theory has had a major influence on mental-health court practice over the past 30 years. According to that theory, the court system must take into account the therapeutic effects of the law and the judicial process to promote adherence to treatment by defendants. The empirical analysis of judicial practices in Quebec shows that courts have been the main actors in the decline of rights in mental health. Therapeutic justice has been dominated by discriminatory, controlling and reformist tendencies. These include the trivialization of concerns about the judicialization of groups living in precarious conditions, inconsistent and lifestyle-oriented legal arguments, and treatment-related judicial decisions.